Peran kearifan lokal terhadap upaya pelestarian Situs Makam Imogiri - Mimi Savitri (Balai Arkeologi Yogyakarta, 2021)
The Imogiri Royal Cemetery Site has provided benefits to the surrounding community, especially abdi dalem as the caretakers of the site for a long time. The local community has created local wisdom in order to survive and continue to enjoy the benefits provided by the site. The question arises are: What is the benefit of the Imogiri Royal Cemetery Site for the surrounding community especially abdi dalem? What kind of local wisdom is created by the abdi dalem at the Imogiri Royal Burial Site? What is the role of local wisdom in the preservation of the Imogiri Royal Burial Site? This research was conducted to examine the role of local wisdom to preserve the Imogiri Royal Burial Site. The data collected using in depth-structure interviews. The analysis was carried out using an interpretive method with hermeneutic model of cultural interpretation. This research generates knowledge that local wisdom has contributed to the preservation of the Imogiri Burial Site. This is important to maintain the sustainability of the site's benefits and to improve people’s welfare.